DOES REFLECTIVE PEDAGOGY MAKE ENVIROMENTAL LACTURER BE BETTER? - Eko Yuliyanto; Fitria Fatichatul Hidayah; Enade Perdana Istyastono; Yosef Wijoyo (Universitas Muhammadiyah Semarang, 2018)
Environmental education is an aspect of education for students who are important to support life in the future. In the learning process there are several factors that influence success in learning. One of them is the ability factor of teaching from a teacher include material, method and learning media. However, there are important factors that need to be considered, namely the ability of teachers to reflect themselves during the learning process. Therefore it is necessary for the research to know the reflection of teachers in the learning process. This study aims to determine the effect of teacher reflection on student learning outcomes. The study involved as many as 15 students of English education. Data obtained in the form of student reflection data, questionnaire value of proenvironment attitudes. The data obtained were analyzed using Paired Samples T-Test. The results showed that the process of reflection that has not been optimal can’t improve the quality of learning.Keywords: pro-environment, reflection of paradigm pedagogy, lecturer, learning